Implementasi Media Pembelajaran Interaktif Berbasis Nearpod untuk Meningkatkan Hasil Belajar Siswa pada Materi Literasi Digital di SMK Model Patriot IV Ciawigebang - Septiyani Nurhasanah; Ahmad Fajri Lutfi (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aimed to analyze the implementation and effectiveness of Nearpod-based interactive learning media on students’ learning outcomes in Digital Literacy subjects at SMK Model Patriot IV Ciawigebang, West Java. The research applied a quantitative approach using a Quasi-Experimental Pretest-Posttest Control Group Design. The sample consisted of 60 tenth-grade MPLB students divided into experimental and control classes. Data were collected through multiple-choice tests and Likert-scale questionnaires, then analyzed using Paired Sample T-Test and Independent Sample T-Test with IBM SPSS Statistics 26. The results showed that the experimental class average score increased from 59.70 to 79.50 with a significance value of 0.000 < 0.05. Student responses also improved from 62.27% to 82.93%, indicating that Nearpod effectively improved students’ learning outcomes.